Research on a path-tracking control system for articulated tracked vehicles - Cui, Da (Strojniški vestnik, 2020)
To achieve path-tracking control of articulated tracked vehicles (ATVs), a control system is designed according to the structural characteristics of the ATVs. The distance deviation and heading angle deviation between the vehicle and the pre-set trajectory are employed as input variables to the controller to control the relative deflection angle of the hinge of the vehicle and the velocity of the sprockets and realize the function of the path tracking control. The effects of two control algorithms are simulated with a RecurDyn/Simulink co-simulation; the results show that the fuzzy proportional-integral-derivative (PID) has a better control effect and precision when compared with the PID method. To verify the effect of the proposed controller, a scaled model test platform that is based on visual navigation is developed. Physical experiments were conducted to show the efficacy of the proposed path-tracking control system, which can effectively track the pre-set trajectory and achieve an optimal control outcome.
Keywords: articulated tracked vehicle; co-simulation; dinamično modeliranje; fuzzy PID controller; kosimulacija; mehki PID-regulator; path tracking; sledenje poti; visual navigation; vizualna navigacija; zgibno gosenično vozilo